Obedience of children to parents suffering from generalized anxiety disorder, jurisprudential and psychological. - Majid Ghandizadeh; Hamid rafiee honar (فقه و حقوق خانواده)
Anxiety disorders are one of the most common psychiatric disorders that cause problems for millions of people every year. The main component in this disorder is "worry". If an individual's parents suffer from generalized anxiety disorder, they are constantly looking for reassurance from their child. And part of these safety-related behaviors take place in the form of instructions that such parents give to their children; On the other hand, obedience to parents is one of the issues raised in the hadiths of the family of Allah, may peace be upon them, the researcher seeks to investigate the characteristics of pervasive anxiety disorder in modern psychology and jurisprudence on the ruling of obeying parents based on the opinion of Shia jurists, the duty of children Specify these parents. In this research, in addition to using the analytical descriptive method, the religious ijtihad method has been used; In the end, it became clear that obeying parents is not absolutely obligatory, but obeying them is obligatory only in two cases, and the children of parents with generalized anxiety disorder do not have to obey their parents' commands and commands, which are caused by their disorder.